Lived Islam in South Asia adaptation, accommodation, and conflict - Ahmad, Imtiaz; Reifeld, Helmut (London Routledge, 2018)
Contributed seminar papers.
Includes bibliographical references and index.
Keywords: Islam -- South Asia -- Congresses; Muslims -- South Asia -- Congresses